تعليميّة النّحو الْعربيّ وبناء النِّظام اللِّسانيّ لدى متعلِّمي الْمرحلة الإلزاميّة. Teaching Arabic Grammar And Building The Linguistic System For The Obligatory Stage Learners - مختارية, عواد; سعاد آمنة, بوعناني (جامعة الوادي - University of Eloued, 2021)
تهدفُ هذه الدِّراسة الْوصفيّة التّحليليّة إلى تبيان أهمِّية تعليميّة النّحو الْعربيّ في بناء النّظام اللِّسانيّ لدى متعلِّمي الْمرحلة الإلزاميّة، والتّأكيد على أنّ التّحويل الْبيداغوجيّ الّذي تشهدهُ منظومتنا التّربويّة ينشدُ بلوغَ أهدافٍ كبرى تتجلى في التّحكّم في اللّغة الْعربيّة كمخرجات للتّعليم الابتدائيّ، لتأتي بعده مساعي التّعليم الْمتوسِّط الّتي تسعى إلى دعم المكتسبات اللّغويّة السّابقة للْمتعلِّمين، وجعل اللّغة الْعربيّة لغة التّواصل، والْخروج بها إلى أفقٍ واسعٍ في مراحل ما بعدَ التّعليم الإلزامي . This analytical descriptive study aims to demonstrate the importance of teaching Arabic grammar in building the linguistic system of obligatory education, and to show that the pedagogical change of our educational system seeks to achieve major objectives in controlling Arabic grammar as primary education outputs. After that comes the endeavors of middle school education that seek to support the learners ’previous linguistic acquisitions, and make of the Arabic language a language of communication, and bring it to a wide horizon in the higher education stages .
مقال
Keywords: النّحو الْعربيّ ; النّظام اللِّسانيّ ; التّعليم ; الْملكة اللّغويّة ; الْمرحلة الإلزاميّة; Arabic Grammar ; the linguistic system ; education ; linguistic competence ; obligatory stage.